Epidemiology of childhood cancer - Terracini Benedetto (BMC, 2011)
Abstract At least in economically developed countries, in the last decades, the incidence of childhood cancer has increased and the increase is unlikely to be an artefact. Causes of the increase have not been identified: a role of preventable environmental exposures is possible. Changes have also occurred in the age distribution of acute lymphoblastic leukaemia. Currently, children with cancer can be successfully treated and cured. However, access to the best therapy differs widely among countries because of the unequal distribution of resources for cancer care. Any double standard in the fate of children with cancer is ethically unacceptable.